2021
DOI: 10.1101/2021.01.14.21249830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge of and Attitudes on Artificial Intelligence in Healthcare: A Provincial Survey Study of Medical Students

Abstract: BackgroundThere has been growing acknowledgement that undergraduate medical education (UME) must play a formal role in instructing future physicians on the promises and limitations of artificial intelligence (AI), as these tools are integrated into medical practice.MethodsWe conducted an exploratory survey of medical students’ knowledge of AI, perceptions on the role of AI in medicine, and preferences surrounding the integration of AI competencies into medical education. The survey was completed by 321 medical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…This result was congruent with findings among medical students worldwide, particularly those in the radiology field (13,14,18,52). Several previous studies found contradict results where the medical students stated that AI could not have a role as an alternative for the physicians in the future (33,53), particularly in some fields that need a "sense of caring" or "art of caring" such as psychological health or aging care (53)(54)(55). Many authors argued that AI should be treated as a virtual assistant rather than being a replacement for physicians in healthcare.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This result was congruent with findings among medical students worldwide, particularly those in the radiology field (13,14,18,52). Several previous studies found contradict results where the medical students stated that AI could not have a role as an alternative for the physicians in the future (33,53), particularly in some fields that need a "sense of caring" or "art of caring" such as psychological health or aging care (53)(54)(55). Many authors argued that AI should be treated as a virtual assistant rather than being a replacement for physicians in healthcare.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, lack of trust in AI was the main contributor to the negative attitude among Chinese people toward the application of AI in healthcare (34). Another study in Canada found that medical students did not believe AI could deliver personalized and empathetic care (33). Thus, we hypothesized that trust would be positively associated with the behavioral intention to use AI systems in medical students.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 92%
See 2 more Smart Citations
“…Most of our respondents (90.3%,) agreed that AI will affect certain medical specialties more than others in terms of specialists being prone to be replaced by AI and job reduction. Similar results were found amongst the respondents in the provincial study by Mehta et al ( 2021 ) (250/288, 87%). We need to further evaluate the main specialties respondents think will be negatively impacted by AI in terms of job opportunities in hopes of uncovering misconceptions, if any, that can be addressed.…”
Section: Discussionsupporting
confidence: 87%